ANALISIS CERPEN “LARA LANA” KARYA DEE LESTARI MENGGUNAKAN PENDEKATAN OBJEKTIF DAN MIMETIK - Bagus Febriana Rahmawan; Syahril Ramadhan; Saproji Saproji (Universitas Maritim AMNI Semarang, 2022)
This study aims to analyze the intrinsic and extrinsic elements in the short story, Lara Lana, by Dee Lestari using an objective and mimetic approach. The research method that I use in this analysis uses a qualitative descriptive method. The resource in this study is the short story Lara Lana by Dee Lestari. The data collection technique used in this study was to read critically and carefully the entire contents of the short story. The data analysis technique is discussing or reviewing the contents of the short story Lara Lana by Dee Lestari. The results of the research are to find intrinsic elements in the form of themes, points of view, plot/plot, setting, characters and characterizations, style of language, and message. You can also find social elements in the phenomena that occur in short stories that are related to real-world life in the form of 1) economic status (poor and rich) 2) bullying 3) love relationships in the novel Lara Lana by Dee Lestari.